2020
DOI: 10.1027/0227-5910/a000630
|View full text |Cite
|
Sign up to set email alerts
|

Grief After Euthanasia and Physician-Assisted Suicide

Abstract: Abstract. Background: Several countries have regulated euthanasia and physician-assisted suicide (PAS). Research has looked at the experiences of patients, family, and professionals. However, little is known of the effects on bereaved individuals. Aims: We aimed to assess (a) what is known about the grief and mental health of people bereaved by euthanasia or PAS and (b) the quality of the research. Method: Systematic review according to PRISMA guidelines with searches in Cinahl, Embase, PsycINFO, Pubmed, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 60 publications
1
40
0
2
Order By: Relevance
“…Although there is little evidence of increased risk of adverse grief or altered mental health outcomes in individuals bereaved by assisted death, 34,35,47 some family members may require additional support through the MAID process and during bereavement. Anticipatory guidance is a proactive intervention to prepare patients and family members for anticipated occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little evidence of increased risk of adverse grief or altered mental health outcomes in individuals bereaved by assisted death, 34,35,47 some family members may require additional support through the MAID process and during bereavement. Anticipatory guidance is a proactive intervention to prepare patients and family members for anticipated occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the impact of PAD on the mental health of bereaved relatives showed that they experienced feeling of isolation and fear of social stigma [ 16 19 ]. However, if they knew that the passing was an autonomous choice, they could accept the death and showed less symptoms of grief and posttraumatic stress disorder [ 16 19 ]. However, research on the impact of PAD on the mental health of bereaved relatives is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the outcome, people bereaved by MAiD (but not MAiD-NT) generally had similar or lower scores on measures of disordered grief, mental health, and posttraumatic stress compared with those who died naturally [36]. However, a Swiss study [37] showed that among members or close friends who were present at an assisted suicide, 13% met the criteria for full Post Traumatic Stress Disorder (PTSD), 6.5% for subthreshold PTSD, and 4.9% for complicated grief, indicating a higher prevalence of psychiatric disorders than the general population.…”
Section: Opinions and Attitudes Of Relatives Of Patients With Psychia...mentioning
confidence: 98%